Politik Hukum: Perbedaan Konsepsi Antara Hukum Barat dan Hukum Islam - Moh. Mahfud MD (Al-Jami'ah Research Centre, 1999)
Efforts to promote Islamic Law in the life of Indonesian Community always appear throughout history. However, the concept of Islamic Law itself has been debated among the Muslims. For that reason, the present author tries to compare the concept of Western Law and Islamic Law. The comparison will be based on JND. Anderson's Islamic Law and the Modem World and Mawdudi's Teori Politik Islam. The author finds that the product of Law was influenced by political configuration. If the political configuration was democratic, the law will be responsive, but, if its political configuration was authoritarian, the product will be conservative. In this context, if the Indonesian Muslims want all products of law influenced by Islamic Law, the Muslims themselves should take part dominantly in the government, but also in the government beurocracy